2016
DOI: 10.1080/01402390.2016.1220367
|View full text |Cite
|
Sign up to set email alerts
|

The Reluctant Atlanticist: France’s Security and Defence Policy in a Transatlantic Context

Abstract: This article introduces the key tenets of French foreign and security policy during the Cold War, and illustrates the deep challenges to the French consensus raised by the emergence of a unipolar system. There is a growing gap between the rhetoric of French security policy, emphasizing 'autonomy' and 'sovereignty' out of habit from the Cold War, and the actual security practices showing a gradual embedding within the transatlantic security structures. In the absence of a new transpartisan grand narrative relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Despite its traditional Gaullist foreign policy discourse, France has since 1945 relied on the American alliance for security (Schmitt 2017;Talmor and Selden 2017;Trachtenberg 2012). The American presence in Europe benefited France by keeping Soviet-Russian power at bay and ensuring that Germany remained benign (Creswell 2002;Soutou 2001).…”
Section: Preventing Chinese Hegemonymentioning
confidence: 99%
“…Despite its traditional Gaullist foreign policy discourse, France has since 1945 relied on the American alliance for security (Schmitt 2017;Talmor and Selden 2017;Trachtenberg 2012). The American presence in Europe benefited France by keeping Soviet-Russian power at bay and ensuring that Germany remained benign (Creswell 2002;Soutou 2001).…”
Section: Preventing Chinese Hegemonymentioning
confidence: 99%
“…131 Furthermore, France's strategic outlook remains shaped partly by its Cold War, Gaullist foreign policy legacy, which was based on the willingness to carve out a "third way" between the Soviet-led and the U.S.-led blocs through some form of accommodation with Moscow while maintaining an independent nuclear force and a French area of inºuence in Africa. 132 The UK, as an offshore seapower, has since the early Cold War concluded that the only way to deter the Soviet Union (and later Russia) is to use the United States as a counterweight. 133 Accordingly, the "special relationship" with the United States, both bilaterally and through NATO, has been the center of gravity of the UK's defense policy-as illustrated by its heavy reliance on U.S. military technology.…”
Section: Assessing the Counterargument: Can Europeans Balance Russia?mentioning
confidence: 99%